Role of FIB-4 for reassessment of hepatic fibrosis burden in referral center - Yun Hwa Roh (Nature Portfolio, 2021)
Abstract Low cut-off of FIB-4 is a widely used formula to exclude advanced liver fibrosis in primary care centers. However, the range of reported threshold of FIB-4 to rule in advanced fibrosis is too broad across etiologies, and no consensus has been reached. In the present study, we investigated the role of FIB-4 for a reassessment of hepatic fibrosis burden in a referral center. We compared the diagnostic performance of FIB-4 among patients with liver disease of various causes and tried to find an optimal cut-off value for predicting advanced fibrosis. Among 1068 patients, the AUROC of FIB-4 to diagnose advanced fibrosis showed no significant difference among the various etiologies of liver disease, ranging from 0.783 to 0.821. The optimal cut-off value obtained by maximizing Youden's index was 2.68, and the sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) for predicting advanced fibrosis were 70.7%, 79.1%, 43.5%, and 92.2%, respectively. The PPV was low in patients with autoimmune disease (6.67%). When we incorporated the new cut-off of FIB-4 into abdominal ultrasound findings, 81% of unnecessary work-ups would be appropriately avoided. In conclusion, the cut-off value of 2.68 showed an acceptable PPV while maintaining a high NPV to predict advanced fibrosis, most etiology except for autoimmune diseases. This result could assist in establishing an appropriate timing to reassess the hepatic fibrosis burden during monitoring in the referral center.